CLINICAL CHARACTERISTICS AND KINESITHERAPY TREATMENT OF CONGENITAL TORTICOLLIS MUSCULAR - Durguti, Zheralldin; Murtezani, Ardiana; Gara, Eqrem; Durguti, Teuta (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Â  Â Objective: Torticollis is a deformity characterized by the lateral flexion of the head to the arm on the side of the localization of deformity and its rotation on the opposite side. The aim of this paper is to identify the clinical characteristics that have an impact on the progression of the congenital muscular cramping, as well as to show the role of kinesitherapy in the treatment of torticollis. Methods: The research was conducted in the Therapyâ€ - Physical Therapy Clinic in Pristina, in the 2-year period since February 2014 until 2016. The total number of infants diagnosed with torticollis is 160, ranging from 0 to 9 months. At the beginning of the research, the examinations of all infants were performed, all the necessary tests, measurements, and motor functions. Afterward, they were rehabilitated for 3 consecutive weeks with 5 sessions per week, a total of 15 sessions for each. After the rehabilitation was completed, over again, the same tests were made as it was done in the beginning. Questionnaires were completed on the first and last visit for all infants. Results: In the first visit of the infants' examination, there was no significant difference between the groups (Chi-test=0.96, p=0.1), whereas in the second examination, after 15 rehabilitation sessions, there was a significant difference in improvement of all the treated groups with kinesiotherapy. Significant result was achieved in mobility where at the beginning of the treatment, there was a very large limitation of neck mobility (different mean = âˆ’31.0Â±10.0.95% CI: 33.7-âˆ’28.2, p<0.001). A small limitation of mobility remained only among some third-degree infants in the 6-9 month age group because of the time appearance for physical treatment was delayed (different mean = âˆ’27.8Â±12.6, 95%, CI: 31.2-âˆ’24.4, p<0.001). Conclusion: From the results of our research on kinesiotherapy with infant toddlers with torticollis, we conclude that kinesitherapy has a primary and very successful effect on the treatment of babies with muscular torticollis.